A New Gene Mutation of PRKAR1A was found in a Carney Complex Case - Ding, Hai-Xuan; Zhao, Xin-Lan; Huang, Ling-Yun; Jiang, Yue; Yang, Li (Journal of Clinical Case Reports and Images, 2021)
A patient with Carney complex is reported with a previously undescribed PRKAR1A mutation. The article situates the variant within PKA pathway biology and clinical phenotype, underscoring the value of genetic testing for diagnosis, counseling, and surveillance.
Keywords: Carney complex; Cushing's syndrome; PPNAD; PRKAR1A